Asymmetric Synthesis of Tetrasubstituted α-Aminophosphonic Acid Derivatives - Aitor Maestro; Xabier del Corte; Adrián López-Francés; Edorta Martínez de Marigorta; Francisco Palacios; Javier Vicario (Molecules, 2021)
Due to their structural similarity with natural α-amino acids, α-aminophosphonic acid derivatives are known biologically active molecules. In view of the relevance of tetrasubstituted carbons in nature and medicine and the strong dependence of the biological activity of chiral molecules into their absolute configuration, the synthesis of α-aminophosphonates bearing tetrasubstituted carbons in an asymmetric fashion has grown in interest in the past few decades. In the following lines, the existing literatures for the synthesis of optically active tetrasubstituted α-aminophosphonates are summarized, comprising diastereoselective and enantioselective approaches.